FILLER TYPES IN STUDENT’S ACADEMIC SPEAKING PRESENTATION: THE USE AND FUNCTION - Anggrarini, Natalia; Efendi, Nasori; Dahlia, Dahlia (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
This study aims to investigate undergraduate students' filler types in academic speaking presentations and how they use filler functions. This qualitative research used observation to analyze the type of fillers used by the students during the presentation and interview to analyze the function of the fillers they used. The participants were 21 undergraduate students of the English Education Department from Universitas Wiralodra. This study reported that the students used lexicalized and unlexicalized fillers during the presentation. Lexicalized fillers are found mostly used by the students with 60,93%. While unlexicalized filler appeared 39.07%. Those fillers functioned to hesitate, empathize, mitigate, edit terms, and create time. Filler is used and functioned by the students to show politeness and create time to plan what to say next. This study implies that the students need various strategies to use fillers properly and understand positive and negative fillers so they can develop their communicative competency. This study suggests further investigation in terms of the use of filler in written language.